Frequency of CXCR3+ CD8+ T-Lymphocyte Subsets in Peripheral Blood Is Associated With the Risk of Paradoxical Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome Development in Advanced HIV Disease - Tibúrcio, Rafael; Narendran, Gopalan; Barreto-Duarte, Beatriz; Queiroz, Artur T. L.; Araújo-Pereira, Mariana; Anbalagan, Selvaraj; Nayak, Kaustuv; Ravichandran, Narayanan; Subramani, Rajasekaran; Antonelli, Lis R. V.; Satagopan, Kumar; Anbalagan, Komathi; et al. (Frontiers in Immunology, 2022)
Background: Tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) is a clinical aggravation of TB symptoms observed among a fraction of HIV coinfected patients shortly after the start of antiretroviral therapy (ART). Of note, TB-IRIS is characterized by exacerbated inflammation and tissue damage that occurs in response to the elevated production of CD4+ T cell-derived IFN-. Nevertheless, the possible participation of CD8+ T cells in TB-IRIS development remains unclear. Methods: We performed a comprehensive assessment of the composition of CD8+ T cell memory subsets and their association with circulating inflammation-related molecules in TB-HIV coinfected patients initiating ART. Results: We found that TB-IRIS individuals display higher frequencies of Antigen-experienced CD8+ T cells during the onset of IRIS and that the levels of these cells positively correlate with baseline mycobacterial smear grade. TB-IRIS individuals exhibited higher frequencies of effector memory and lower percentages of naïve CD8+ T cells than their Non-IRIS counterparts. In both TB-IRIS and Non-IRIS patients, ART commencement was associated with fewer significant correlations among memory CD8+ T cells and cells from other immune compartments. Networks analysis revealed distinct patterns of correlation between each memory subset with inflammatory cytokines suggesting different dynamics of CD8+ T cell memory subsets reconstitution. TB-IRIS patients displayed lower levels of memory cells positive for CXCR3 (a chemokine receptor that plays a role in trafficking activated CD8+ T cells to the tissues) than Non-IRIS individuals before and after ART. Furthermore, we found that CXCR3+ naïve CD8+ T cells were inversely associated with the risk of TB-IRIS development. On the other hand, we noticed that the frequencies of CXCR3+ effector CD8+ T cells were positively associated with the probability of TB-IRIS development. Conclusion: Our data suggest that TB-IRIS individuals display a distinct profile of memory CD8+ T cell subsets reconstitution after ART initiation. Moreover, our data point to a differential association between the frequencies of CXCR3+ CD8+ T cells and the risk of TB-IRIS development. Collectively, our findings lend insights into the potential role of memory CD8+ T cells in TB-IRIS pathophysiology.